Photoredox Imino Functionalizations of Olefins - Davies, Jacob (Angew Chem Int Ed Engl, 2017)
Shown herein is that polyfunctionalized nitrogen heterocycles can be easily prepared by a visible‐light‐mediated radical cascade process. This divergent strategy features the oxidative generation of iminyl radicals and subsequent cyclization/radical trapping, which allows the effective construction of highly functionalized heterocycles. The reactions proceed efficiently at room temperature, utilize an organic photocatalyst, use simple and readily available materials, and generate, in a single step, valuable building blocks that would be difficult to prepare by other methods.